2022
DOI: 10.1021/acs.est.2c00623
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Trade Helps to Alleviate Global Carbon Emission Pressure

Abstract: Global dairy production, consumption, and trade are growing rapidly, driven by population and per capita income growth and increasing health concerns mainly from developing countries, which has aroused concerns about the related carbon emission (mostly in the form of methane) increase. If all of the dairy products consumed were produced locally/domestically in the developing countries/economies (a counterfactual scenario), the carbon emissions in 2018 would be 28 Mt CO2-equiv higher than its status quo (a fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In contrast, increasing the production and trade of eggs, vegetables, and root crops could help close the nutrient gap with lower GHG emissions in most countries [34]. Trade in dairy products not only aids in improving child stunting [35] but also reduces GHG emissions [36]. Therefore, the trade in livestock products could be directed toward dairy products and eggs by reducing tariffs on these items and increasing tariffs on red meat.…”
Section: Future Implicationsmentioning
confidence: 99%
“…In contrast, increasing the production and trade of eggs, vegetables, and root crops could help close the nutrient gap with lower GHG emissions in most countries [34]. Trade in dairy products not only aids in improving child stunting [35] but also reduces GHG emissions [36]. Therefore, the trade in livestock products could be directed toward dairy products and eggs by reducing tariffs on these items and increasing tariffs on red meat.…”
Section: Future Implicationsmentioning
confidence: 99%
“…However, not all possible impacts of the dairy trade are negative. Wu et al report that the dairy trade alleviates the pressure on global carbon emissions [18][19][20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Subak showed that the methane leakage associated with international trade of rice, meat and milk products can jeopardize the effectiveness of Framework Convention on Climate Change (Subak, 1995). More recent studies uncovered the role of international meat (Caro et al, 2014), dairy (Wu et al, 2022) as well as general commodity trade (Fernández-Amador et al, 2020;Wang et al, 2019;Yan et al, 2021) in redistributing regional methane emissions.…”
Section: Introductionmentioning
confidence: 99%